Uma reflexão a partir de Mt 18,10 e das tradições judaicas: Uma reflexão a partir de Mt 18,10 e das tradições judaicas - Heitor Carlos Santos Utrini (2023)
This article aims to shed light on the text of Matthew 18,10 from the theme of angelology in the Jewish tradition. Angelic figures are present in both the OT and the NT. The New Testament texts make a re-reading of the theme according to the traditions originating from the OT and the Jewish tradition as a whole, in which it is possible to perceive several angelic figures that perform different functions. However, the text of Mt 18:10 seems to bring a different idea, as Jesus exhorts not to despise the little ones because his angels continually see the face of the Father in heaven. From the analysis of biblical and extra-biblical texts, the saying of Jesus will be analyzed to understand the existing traditions behind the pericope and to broaden the understanding about it.